What is driving the 'African Growth Miracle'? - Kenneth Harttgen; Margaret McMillan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We show that much of Africa s recent growth and poverty reduction can be traced to a substantive decline in the share of the labor force engaged in agriculture. This decline has been accompanied by a systematic increase in the productivity of the labor force, as it has moved from low productivity agriculture to higher productivity manufacturing and services. These declines have been more rapid in countries where the initial share of the labor force engaged in agriculture is the highest and where commodity price increases have been accompanied by improvements in the quality of governance.
Keywords: O13; O40; Q16; 330